Efektivitas Program Dapur Kuliner Nusantara BAZNAS Kabupaten Subang dalam Pemberdayaan Ekonomi UMKM pada Masa Pandemi Covid-19 - Fitriani Millenia Onesha; Asnita Frida Sebayang (UNISBA Press, 2022)
Abstract. The emergence of the Corona Virus Disease (Covid-19) at the end of 2019 had an impact without exception for all economic sectors, one of which was the MSME sector in the culinary sector. BAZNAS presents solutions with empowerment through the Dapur Kuliner Nusantara Program. Empowerment is an effort to empower the weak to increase their ability and independence in changing the community's economy to a better direction. This program involves 19 SMEs in rice stalls who are given assistance in the form of a stimulus to purchase food packages in a certain amount and serve as production partners. This study uses a quantitative descriptive method. The data used are primary data obtained through a survey of 19 rice stall entrepreneurs in Subang Regency as key informants. The analysis was carried out quantitatively by scoring the results of key informants' answers using a Likert scale with 4 indicators, namely target accuracy, goal achievement, real change and program monitoring. The results of the study found that the average results of the effectiveness of the DKN program were 3.18% with effective criteria. Key informants assessed that the program was running effectively in accordance with the stated objectives and was successfully achieved. The target accuracy indicator is the indicator that has the highest yield of 3.68% with very effective criteria. The informant considered that the program targets were in accordance with the needs of business actors during the Covid-19 pandemic. Abstrak. Kemunculan Corona Virus Desease (Covid-19) pada akhir tahun 2019 memberikan dampak tanpa terkecuali seluruh sektor perekonomian, salah satunya sektor UMKM bidang kuliner. BAZNAS menghadirkan solusi dengan pemberdayaan melalui Program Dapur Kuliner Nusantara. Pemberdayaan adalah suatu upaya memberdayakan yang lemah untuk meningkatkan kemampuan dan kemandirian dalam merubah perekonomian masyarakat ke arah yang lebih baik. Program ini melibatkan 19 pelaku UMKM warung nasi yang diberikan bantuan berupa stimulus pembelian paket makanan dalam jumlah tertentu dan dijadikan sebagai mitra produksi.Penelitian ini menggunakan metode deskripsif kuantitatif. Data yang digunakan merupakan data primer yang didapat melalui survei terhadap 19 pelaku usaha warung nasi di Kabupaten Subang sebagai informan kunci. Analisis dilakukan secara kuantitatif dengan melakukan skoring terhadap hasil jawaban informan kunci menggunakan skala likert dengan 4 indikator yaitu ketepatan sasaran, tercapainya tujuan, perubahan nyata dan pemantauan program. Hasil penelitian menemukan bahwa rata-rata hasil efektivitas program DKN adalah 3,18% dengan kriteria efektif. Informan kunci menilai bahwa program berjalan efektif sesuai dengan tujuan yang telah ditetapkan dan berhasil dicapai. Indikator ketepatan sasaran adalah indikator yang memiliki hasil tertinggi yakni sebesar 3,68% dengan kriteria sangat efektif. Informan menilai bahwa sasaran program sesuai dengan kebutuhan pelaku usaha di masa pandemi Covid-19.